Acromioclavicular joint separation - Devan Pandya, BS; John Costumbrado, MD, MPH (Journal of Education and Teaching in Emergency Medicine, 2018)
History of present illness: A 30-year-old male was brought in by ambulance to the emergency department as a trauma activation after a motorcycle accident. The patient was the helmeted rider of a motorcycle traveling at an unknown speed when he lost control and was thrown off his vehicle. He denied loss of consciousness, nausea, or vomiting. The patient’s vital signs were stable and his only complaint was pain around his left shoulder. On exam, the patient had a prominent left clavicle without skin compromise. He had adequate range of motion in the left shoulder with moderate pain, and his left upper extremity was neurovascularly intact.